PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, LOYALITAS KERJA, DAN SELF EFFICACY, TERHADAP KINERJA KARYAWAN PADA LEMBAGA PEMASYARAKATAN (LAPAS) KELAS II A PAMEKASAN - Ahmat Riki Sukron; M Sihab Ridwan (Cahaya Ilmu Bangsa, 2024)
The aim of the research is to determine and analyze the influence of transformational leadership style, work loyalty and self-efficacy on the performance of Class IIA Pamekasan prison employees. With the required population of 60 employees using a quantitative research approach, and samples using non-probability purposive sampling techniques and data collection for this research is primary data and secondary data from questionnaire results and data analysis using multiple linear regression analysis methods, t-test, F-test. The research results show that individually or partially (t-test) on variable. 1.) There is no discernible effect of the transformative leadership style (X1) on worker performance because with a sig value of 0.788 > 0.05 and tcount of 0.270 < ttable 1.672. 2). Work Loyalty (X2) has a significant effect on Employee Performance, with a value of sig. a number of 0.001 < 0.05 and t-count of 3,517 > t-table 1.672. 3). Self-efficacy (X3) has a significant impact on employee performance, with a sig value of 0.001 < 0.05 and tcount of 6.578 > ttable 1.672. And the results of the F test show that the significance value is 0.001 < 0.05 with an F-Calculated value of 151,288 > F-Table 4.013. Thus it can be said that H0 is rejected while H1 is accepted. Therefore, the three factors that are independent variables have a simultaneous and quite large influence on the performance of employees at the Class IIA Pamekasan Penitentiary.